Answer:
(-2x²- 4x + 2) - (-6x + 2) = -2x²+ 2x
Step-by-step explanation:
(-2x²- 4x + 2) - (-6x + 2)=
= -2x²- 4x + 2 + 6x - 2 =
= -2x²+ 2x
1.g(f(x)) = g(x^3 - 27)(x)
=x^3 - 27 -3
=x^3 -30
Matched with letter A.
2.f(x^2(x))= (x^3 - 27)^2
=(x^3 - 27)(x^3 - 27)
=x^6 - 54x^3 + 729
Matched with letter C
3. f(g(x))= f(x - 3)(x)
=(x - 3)^3 - 27
=[(x - 3)(x - 3)(x - 3)]-27
=x^3- 9^2+ 27x- 54
Matched with letter B.
4. (f(x))2 = (x^3 - 27)^2
=(x^3 - 27)(x^3 - 27)
=x^6 - 54x^3 + 729
Matched with letter C
Answer:
(10x3)x12
Step-by-step explanation:
There can I get brainliest
Answer:
6 percent
Step-by-step explanation: